Assessment of Nutritional Strategies using Slow-Release Urea to Enhance Growth Efficiency in Arabi Lambs - Al-Ameri , Marwah Th. G.; Al-Galbi , Hanaa A. J.; Nasser , Amera K. (American Journal of Botany and Bioengineering, 2025)
The study aimed to evaluate the effect of supplementing slow-release urea at different levels (1%, 1.5%, 2%) in the diets of Arabi lambs on productive performance. No significant differences were observed in initial body weight, while final body weight increased from 36.10 kg in the control group (T1) to 39.83 kg in the 2% urea group (T4). Daily weight gain also improved from 129.9 g/day in T1 to 187.8 g/day in T4, and total weight gain increased from 9.10 kg to 13.15 kg. Although daily feed intake did not differ significantly among treatments (1.00–1.04 kg), feed conversion ratio improved significantly (P<0.05), decreasing from 7.72 kg feed/kg gain in T1 to 5.57 kg in T4. These results suggest enhanced feed utilization efficiency, likely due to improved energy–nitrogen balance that supports microbial activity in the rumen.